Pengaruh Permainan Balok Angka Terhadap Kemampuan Mengenal Lambang Bilangan Kelompok A TK Pembina HKBP Tarutung - Rohani Purba; Adiani Hulu; Julita Herawati P; Hisardo Sitorus; Emmi Silvia Herlina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The aim of this research was to determine the effect of the number block game on the ability to recognize number symbols for group A TK Pembina HKBP Tarutung. The method used in this research is a descriptive quantitative research method. The population was all children from group A of the TK Pembina HKBP totaling 25 people and all of them were used as research respondents. Data was collected using positive closed observation items totaling 13 items namely 7 items for variabel X and 6 items variabel Y. The results of data analysis show that there is a positive influence from the number block game on the ability to recognize number symbols for group A TK Pembina HKBP Tarutung: 1) Test the analysis requirements: a) test a positive relationship the value obtained is rxy = 0,564 > rtabel(=0,05,n=25) = 0,396, Thus it is know that there is a positive relationship between variable X and variable Y. b) Test significant relationship value obtained thitung= 3,276 > ttabel(=0,05,dk=n-2=23)= 2,069 thus there is a significant relationship between variable X and variable Y. c) Regression coefficient of determination test (r2) = 31,8%.2) Influence test: Regression equation test, obtained regression equation . Thus Ha that is there is an influence of the number block game on the ability to recognize number symbols for group A TK Pembina HKBP Tarutung is accepted and H0 is rejected.